Catalyst for long-acting composite three-way catalyst and preparation method thereof
By using MCM-41 molecular sieve support in a three-way catalyst to coat activated alumina, dopant elements such as Cu and Mn, and combining noble metal rhodium to form a perovskite-type catalyst, the problem of poor results in treating ethanol automobile exhaust is solved, and more efficient and long-term catalytic performance and cost savings are achieved.
Patent Information
- Application Number
- CN202411004002.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing three-way catalysts are not effective when treating ethanol automobile exhaust, and the catalyst has poor thermal stability and mechanical properties, making it difficult to meet higher automobile exhaust treatment needs.
A catalyst for a long-acting composite three-way catalyst is used. The preparation method includes coating activated alumina with MCM-41 molecular sieve as a support, and combining noble metal rhodium by doping elements such as Cu and Mn to form a perovskite catalyst.
It improves the catalytic capacity of the catalyst and the absorption and catalytic capacity of organic pollutants such as ethanol, enhances the conversion effect of hydrocarbons, reduces the amount of precious metals, and improves the long-term effectiveness and cost-effectiveness of the catalyst.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of automobile exhaust treatment, and in particular relates to a catalyst for a long-acting composite three-way catalytic converter and a preparation method thereof. Background Art
[0002] As people's living standards continue to improve, cars have become the mainstream means of transportation and are widely used. However, with the increase in the number of cars, the air pollution caused by automobile exhaust is becoming increasingly serious, and has become one of the main pollution sources in large cities. The main pollutants in automobile exhaust are harmful gases such as carbon monoxide (CO), hydrocarbons (HC) and nitrogen oxides (NOx). These gases not only pollute the environment, but also have great harm to the human body. Therefore, the control of automobile exhaust pollution is becoming increasingly important.
[0003] The three-way catalytic converter is the most important off-board purification device installed in the automobile exhaust system. The three-way catalytic converter is equipped with a catalyst, which is usually composed of precious metals such as platinum (Pt), rhodium (Rh) and palladium (Pd). These catalysts promote chemical reactions at high temperatures. It can convert harmful gases such as CO, HC and NOx emitted from automobile exhaust into harmless carbon dioxide, water and nitrogen through oxidation and reduction. Since this catalyst can simultaneously convert the three main harmful substances in the exhaust gas into harmless substances, it is called a three-way catalytic converter.
[0004] Fossil fuel depletion, the impact of global warming and energy concerns are all issues facing the current energy sector. Ethanol is one of the most promising options. Adding ethanol to gasoline as a vehicle fuel has some advantages and can reduce dependence on oil imports. However, the exhaust gas emitted by ethanol gasoline vehicles contains harmful substances such as incompletely burned ethanol, acetaldehyde, ether, ketones and ethyl acetate. The catalyst in the conventional three-way catalytic converter cannot effectively remove these harmful substances, which limits the application of the three-way catalytic converter in the field of ethanol vehicle exhaust treatment. In addition, the catalyst in the three-way catalytic converter has poor thermal stability and mechanical properties. Therefore, the above problems need to be solved to meet the higher demands in the field of vehicle exhaust treatment technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a catalyst for a long-acting composite three-way catalytic converter and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A long-acting composite three-way catalytic converter catalyst is prepared by the following steps:
[0008] S1, MCM-41 molecular sieve and aluminum sulfate solution are mixed, ammonia water is added dropwise and stirred continuously, and after the addition is completed, stirring is continued at 80°C for 2 hours, and the mixture is allowed to stand for precipitation, filtered and separated, and washed with distilled water for 4-5 times, dried, and then placed in a muffle furnace and a protective gas is introduced, and calcined to obtain a carrier;
[0009] S2. Put La(NO 3 ) 3 6H 2 O, Cu(NO 3 ) 2 ,Ni(NO 3 ) 2 6H 2 O and Mn(NO 3 ) 2 ·4H 2 O is added into deionized water, stirred until the solid is completely dissolved, citric acid is added, and ammonia water is added dropwise to adjust the pH of the solution to 8-8.5, the temperature is increased to 70-80°C, and stirred until it becomes a wet gel, vacuum dried, cooled, added into a muffle furnace for calcination, and ground to obtain a perovskite powder;
[0010] S3, mixing rhodium nitrate with deionized water, adding a dispersant and stirring for 1-5 hours, then adding dropwise to the perovskite powder obtained in step S2, standing for 1-5 hours, drying in an oven at 100° C. for 12 hours, and then calcining in a muffle furnace to obtain a powder;
[0011] S4. Add deionized water to the powder obtained in step S3 to form a slurry. After ball milling, add aluminum gel to the slurry and coat it on the carrier obtained in step S1. After coating, dry it in an oven at 200° C. for 1-5 hours and calcine it in a muffle furnace to obtain a catalyst.
[0012] Furthermore, in step S1, the ratio of the amount of MCM-41 molecular sieve, aluminum sulfate solution, and ammonia water is 5-8 g: 20-30 mL: 10-15 mL.
[0013] Furthermore, the protective gas in step S1 is one of nitrogen and helium.
[0014] Furthermore, the calcination conditions in step S1 are 500-550° C. and calcination time is 4-6 hours.
[0015] Further, in step S2, La(NO 3 ) 3 6H 2 O, Cu(NO 3 ) 2 ,Ni(NO 3 ) 2 6H 2 O、Mn(NO3 ) 2 ·4H 2 The ratio of O, deionized water and citric acid is 14-16g:12-14g:17-19g:18-20g:200mL:1-2g.
[0016] Furthermore, the calcination conditions in step S2 are 700-750° C. and calcination time is 2-4 hours.
[0017] Furthermore, in step S3, the ratio of rhodium nitrate, deionized water and dispersant is 5-6 g:100 mL:1-3 g.
[0018] Furthermore, the dispersant in step S3 is one of paraffin and polyvinyl pyrrolidone.
[0019] Furthermore, the calcination conditions in step S3 are 550-600° C. and calcination time is 3-6 hours.
[0020] Furthermore, the particle size of the ball milling in step S4 is controlled at 10-15 μm.
[0021] Furthermore, the calcination conditions in step S4 are 600-800° C. and calcination time is 4-8 hours.
[0022] The prepared catalyst carrier uses MCM-41 molecular sieve with good texture performance, high specific surface area, multiple pores, and uniform pore size distribution, which can effectively absorb and catalyze gaseous organic pollutants; the active alumina is coated on the surface of the MCM-41 molecular sieve by in-situ generation, which increases the dispersion of active centers and enables the catalyst to have more chemical adsorption sites for ethanol molecules;
[0023] The prepared catalyst is a perovskite catalyst. Due to the addition of the rare earth element La, the conversion effect of the catalyst on sulfides is improved, the anti-poisoning ability of the catalyst is enhanced, and the catalytic ability of the catalyst is improved; in addition, the perovskite catalyst is doped with Cu at the A position and Mn at the B position, which can significantly enhance the conversion effect of the catalyst on hydrocarbons and improve the catalytic performance of the catalyst; not only that, combining the noble metal rhodium with the perovskite compound can play a good stabilizing role on the noble metal rhodium, prevent the noble metal rhodium from high-temperature sintering or high-temperature evaporation, and prevent the noble metal rhodium from reacting with the carrier, thereby improving the long-term effectiveness of the catalysis, reducing the amount of noble metal used, and saving costs.
[0024] Beneficial effects of the present invention:
[0025] 1. The catalyst carrier prepared by the present invention coats the surface of MCM-41 molecular sieve with activated alumina, thereby improving the catalytic ability of the catalyst and the absorption and catalytic ability of the catalyst for organic pollutants such as ethanol;
[0026] 2. The prepared catalyst is a perovskite catalyst. The catalytic ability of the catalyst is greatly enhanced by doping Cu and Mn, and the amount of precious metals used is reduced, saving costs;
[0027] Therefore, the catalyst prepared by the present invention has strong catalytic performance, high catalytic activity to organic pollutants such as ethanol, and low cost, and has important application value in the field of automobile exhaust treatment technology. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] S1, 5g MCM-41 molecular sieves were mixed with 20mL aluminum sulfate solution (mass fraction 18%), 10mL ammonia water (mass fraction 14%) was added dropwise and stirred continuously. After the addition was completed, stirring was continued at 80°C for 2h, and the mixture was allowed to stand for precipitation. The mixture was separated by filtration using a vacuum pump, washed with distilled water for 4 times, dried, and then placed in a muffle furnace and introduced with nitrogen, and calcined at 500°C for 4h to obtain a carrier;
[0031] S2, 14gLa(NO 3 ) 3 6H 2 O, 12gCu(NO 3 ) 2 、17gNi(NO 3 ) 2 6H 2 O and 18gMn(NO 3 ) 2 ·4H 2 O was added into 200 mL of deionized water, stirred until the solid was completely dissolved, 1 g of citric acid was added, and ammonia water was added dropwise to adjust the solution pH to 8, the temperature was raised to 70°C, and stirred until it became a wet gel, vacuum dried, cooled, added into a muffle furnace at 700°C, calcined for 2 h, and ground to obtain a perovskite powder;
[0032] S3, 5 g of rhodium nitrate was mixed with 100 mL of deionized water, 1 g of polyvinyl pyrrolidone was added and stirred for 1 h, and then the mixture was added dropwise to the perovskite powder obtained in step S2, and allowed to stand for 1 h, dried in an oven at 100 ° C for 12 h, and then placed in a muffle furnace and calcined at 550 ° C for 3 h to obtain a powder;
[0033] S4. Add deionized water to the powder obtained in step S3 to form a slurry. After ball milling (the particle size is controlled at 10 μm), aluminum gel (1 g / L) is added to the slurry and coated on the carrier obtained in step S1. After coating, it is dried in an oven at 200° C. for 1 h, and placed in a muffle furnace and calcined at 600° C. for 4 h to obtain a catalyst.
[0034] Example 2
[0035] S1, 6.5g MCM-41 molecular sieve was mixed with 25mL aluminum sulfate solution (mass fraction 18%), 12.5mL ammonia water (mass fraction 14%) was added dropwise and stirred continuously. After the addition was completed, stirring was continued at 80°C for 2h, and the mixture was allowed to stand for precipitation. The mixture was separated by filtration using a vacuum pump, washed with distilled water for 5 times, dried, and then placed in a muffle furnace and passed with helium, and calcined at 525°C for 5h to obtain a carrier;
[0036] S2, 15gLa(NO 3 ) 3 6H 2 O, 13gCu(NO 3 ) 2 、18gNi(NO 3 ) 2 6H 2 O and 19gMn(NO 3 ) 2 ·4H 2 O was added into 200 mL of deionized water, stirred until the solid was completely dissolved, 2 g of citric acid was added, and ammonia water was added dropwise to adjust the pH of the solution to 8.5, the temperature was raised to 75°C, and stirred until it became a wet gel, vacuum dried, cooled, added into a muffle furnace at 725°C, calcined for 3 h, and ground to obtain a perovskite powder;
[0037] S3, 5.5 g of rhodium nitrate was mixed with 100 mL of deionized water, 2 g of polyvinyl pyrrolidone was added and stirred for 2.5 h, and then the mixture was added dropwise to the perovskite powder obtained in step S2, and allowed to stand for 3.5 h, dried in an oven at 100 ° C for 12 h, and then placed in a muffle furnace and calcined at 575 ° C for 4 h to obtain a powder;
[0038] S4. Add deionized water to the powder obtained in step S3 to form a slurry. After ball milling (the particle size is controlled at 12.5 μm), aluminum gel (3 g / L) is added to the slurry and coated on the carrier obtained in step S1. After coating, it is dried in an oven at 200° C. for 2.5 h, and placed in a muffle furnace and calcined at 700° C. for 6 h to obtain a catalyst.
[0039] Example 3
[0040] S1, 8g MCM-41 molecular sieves were mixed with 30mL aluminum sulfate solution (mass fraction 18%), 15mL ammonia water (mass fraction 14%) was added dropwise and stirred continuously. After the addition was completed, stirring was continued at 80°C for 2h, and the mixture was allowed to stand for precipitation. The mixture was separated by filtration using a vacuum pump, washed with distilled water for 5 times, dried, and then placed in a muffle furnace and introduced with helium, and calcined at 550°C for 6h to obtain a carrier;
[0041] S2, 16gLa(NO 3 ) 3 6H 2 O, 14gCu(NO 3 ) 2 、19gNi(NO 3 ) 2 6H 2 O and 20gMn(NO 3 ) 2 ·4H 2 O was added into 200 mL of deionized water, stirred until the solid was completely dissolved, 2 g of citric acid was added, and ammonia water was added dropwise to adjust the pH of the solution to 8.5, the temperature was raised to 80°C, and stirred until it became a wet gel, vacuum dried, cooled, added into a muffle furnace at 750°C, calcined for 4 h, and ground to obtain a perovskite powder;
[0042] S3, 6 g of rhodium nitrate was mixed with 100 mL of deionized water, 3 g of paraffin was added and stirred for 5 h, and then the mixture was added dropwise to the perovskite powder obtained in step S2, and allowed to stand for 5 h, dried in an oven at 100 ° C for 12 h, and then placed in a muffle furnace and calcined at 600 ° C for 6 h to obtain a powder;
[0043] S4. Add deionized water to the powder obtained in step S3 to form a slurry. After ball milling (the particle size is controlled at 15 μm), aluminum gel (5 g / L) is added to the slurry and coated on the carrier obtained in step S1. After coating, it is dried in an oven at 200° C. for 5 h, and placed in a muffle furnace and calcined at 800° C. for 8 h to obtain a catalyst.
[0044] Comparative Example 1
[0045] A commercially available cerium carbonate powdery three-way catalyst produced by Jining Shunhua Chemical Co., Ltd. was used.
[0046] Comparative Example 2
[0047] The difference from Example 3 is that step S1 is omitted, cordierite is used as a carrier in step S4, and the remaining steps are the same as those in Example 3 to obtain a catalyst.
[0048] The catalysts of Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests:
[0049] After the catalyst samples were aged for 48 hours under the same conditions as the GMAC875 bench aging cycle of General Motors, the vehicle emission test was carried out according to the ECE+EUDC cycle to test the vehicle's emissions of hydrocarbons, carbon monoxide and nitrogen oxides;
[0050] The catalyst sample was placed in a continuous flow fixed bed quartz reactor and heated at 400 °C with air (30 mL min -1 ) was purged for 5 h, and ethanol simulation gas (50 mL of air was passed into the saturator to bring out ethanol) was used for activity evaluation; the concentration of each product at the outlet was detected using a gas chromatograph (SC-2000G, Chongqing Chuanyi Analytical Instrument Co., Ltd., FID, KB-wax capillary column), and the conversion rate of ethanol was calculated;
[0051] The measured results are shown in the following table:
[0052] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Hydrocarbon (g / km) 0.0294 0.0287 0.0286 0.0334 0.327 Carbon monoxide (g / km) 0.521 0.515 0.511 0.719 0.712 Nitrogen oxides (g / km) 0.0299 0.0289 0.0284 0.0647 0.0636 Ethanol conversion rate / % 84.4 85.1 85.6 62.4 60.7
[0053] It can be seen from the above table that the catalyst prepared in the embodiment of the present invention has strong catalytic performance for hydrocarbons, carbon monoxide, nitrogen oxides and ethanol, and has important application value in the field of automobile exhaust treatment technology.
[0054] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0055] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a catalyst for a long-acting composite three-way catalytic converter, characterized in that: The following steps are involved: S1, mixing MCM-41 molecular sieve with aluminum sulfate solution, adding ammonia water dropwise and stirring continuously, after the addition is completed, stirring is continued at 80°C for 2h, standing for precipitation, filtering and separating, washing, drying, and then placing it in a muffle furnace and passing protective gas, roasting to obtain a carrier; S2. Add La(NO3)3·6H2O, Cu(NO3)2, Ni(NO3)2·6H2O and Mn(NO3)2·4H2O to deionized water, stir, add citric acid, and drop ammonia water to adjust the solution pH to 8-8.5, increase the temperature to 70-80°C, stir until it becomes a wet gel, dry, cool, roast, grind, and obtain a perovskite powder; S3, mixing rhodium nitrate with deionized water, adding a dispersant and stirring, and dropping it into the perovskite powder obtained in step S2, standing, drying, and calcining to obtain a powder; S4, adding deionized water to the powder obtained in step S3 to form a slurry, adding aluminum gel after ball milling, and coating the slurry on the carrier obtained in step S1. After coating, drying and calcining are performed to obtain a catalyst.
2. The method for preparing a long-acting composite three-way catalytic converter catalyst according to claim 1, characterized in that: In step S1, the ratio of the amount of MCM-41 molecular sieve, aluminum sulfate solution, and ammonia water is 5-8 g: 20-30 mL: 10-15 mL.
3. The method for preparing a catalyst for a long-acting composite three-way catalytic converter according to claim 1, characterized in that: The calcination conditions in step S1 are 500-550° C. and 4-6 hours.
4. The method for preparing a catalyst for a long-acting composite three-way catalytic converter according to claim 1, characterized in that: In step S2, the ratio of La(NO3)3·6H2O, Cu(NO3)2, Ni(NO3)2·6H2O, Mn(NO3)2·4H2O, deionized water and citric acid is 14-16g:12-14g:17-19g:18-20g:200mL:1-2g.
5. The method for preparing a catalyst for a long-acting composite three-way catalytic converter according to claim 1, characterized in that: The calcination conditions in step S2 are 700-750° C. and calcination for 2-4 hours.
6. The method for preparing a catalyst for a long-acting composite three-way catalytic converter according to claim 1, characterized in that: In step S3, the ratio of rhodium nitrate, deionized water and dispersant is 5-6g:100mL:1-3g.
7. The method for preparing a catalyst for a long-acting composite three-way catalytic converter according to claim 1, characterized in that: The dispersant in step S3 is one of paraffin and polyvinyl pyrrolidone.
8. The method for preparing a catalyst for a long-acting composite three-way catalytic converter according to claim 1, characterized in that: The calcination conditions in step S3 are 550-600° C. and calcination time is 3-6 hours.
9. The method for preparing a catalyst for a long-acting composite three-way catalytic converter according to claim 1, characterized in that: The calcination conditions in step S4 are 600-800° C. and 4-8 hours.
10. A catalyst for a long-acting composite three-way catalytic converter, characterized in that: Prepared according to the method according to any one of claims 1 to 9.